2007
DOI: 10.1039/b612876a
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium(iii) complexes of mono- and diethyl esters of monophosphonic acid analogue of DOTA as potential MRI contrast agents: solution structures and relaxometric studies

Abstract: Two new macrocyclic DOTA-like chelates containing one phosphonate pendant arm were synthesised as potential contrast agents for MRI (magnetic resonance imaging). The chelates bind to the lanthanide(III) in an octadentate manner, via four nitrogen atoms, three carboxylate and one phosphonate oxygen atoms. Solution structures of [Ln(do3ap(OEt2))(H(2)O)] and [Ln(do3ap(OEt))(H(2)O)](-) were studied using (31)P and (1)H NMR spectroscopy and SAP (square-antiprismatic)/TSAP (twisted square-antiprismatic) isomerism wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 53 publications
5
71
0
Order By: Relevance
“…[46] The observed relaxivities of all [Gd(DOTP R )] -complexes fall into the narrow region 2.1-2.8 s -1 m -1 (20 MHz, 37°C). The relaxivity of Gd III complexes with DOTA-like ligands having one inner-sphere water molecule is higher (≈ 4), [22,54] although in these cases the inner-sphere contributions are about 50 % of the final value, whereas the second-sphere water molecules of the presently studied complexes have a contribution of only 10-15 % to the total relaxivity. The ligands studied differ in the size and hydrophilic/hydrophobic character of the substituents on the phosphorus atoms and in the isomeric distributions of their complexes in solution.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[46] The observed relaxivities of all [Gd(DOTP R )] -complexes fall into the narrow region 2.1-2.8 s -1 m -1 (20 MHz, 37°C). The relaxivity of Gd III complexes with DOTA-like ligands having one inner-sphere water molecule is higher (≈ 4), [22,54] although in these cases the inner-sphere contributions are about 50 % of the final value, whereas the second-sphere water molecules of the presently studied complexes have a contribution of only 10-15 % to the total relaxivity. The ligands studied differ in the size and hydrophilic/hydrophobic character of the substituents on the phosphorus atoms and in the isomeric distributions of their complexes in solution.…”
Section: Discussionmentioning
confidence: 92%
“…[25] It has been shown recently that the second-sphere contribution to the overall relaxivity is significant even in complexes of H 5 DTPA (H 5 DTPA = 1,4,7-triazaheptane-1,1,4,7,7-pentaacetic acid, Scheme 1) [26] or H 4 DOTA derivatives containing only one phosphonic/phosphinic acid group. [20][21][22] This contribution was found to be more pronounced when complexes of these monophosphorus acid ligands were bound to macromolecules. [27,28] Theoretical approaches to treat the second-sphere hydration have confirmed that phosphonic acid groups enhance the hydration of complexes of DOTAlike ligands [29] as well as of open-chain ligands.…”
Section: Dotpmentioning
confidence: 90%
“…The yields for 3 and 4, 18% and 35%, respectively, were lower than those generated for 1 and 2, which may be attributable to interaction of the carboxylic acid pendant arms with the copper catalyst. [19,20]. In the spectra of complexes 3 and 4, there is a small broad resonance at 10.4 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…However, the contribution of water molecules present for long lifetimes in the second-sphere of complexes can also be significant [22,23]. This is particularly true for polyaminophosphonate complexes, due to hydrogen bonding of water molecules with the phosphonate oxygens [24]. This effect is even more noticeable in phosphonate complexes with no inner-sphere water, such as Gd(DOTMP) [26].…”
Section: Proton Relaxivitiesmentioning
confidence: 91%